The Role of Social Problems in Legal Issues (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
A citizen has the right to engage in entrepreneurial activity from the moment of registration as a private entrepreneur. Documents submitted on business activity may not be registered due to the non-compliance of the information content in them with the requirements of the law. In this case, it is allowed to appeal to the commercial court.